The Development of Interactive E-Book on Plants Growth and Development Materials to Train Digital Literacy of Students - Alfina Damayanti; Yuliani Yuliani (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2023)
The era of the 21st century is the era where information in digital form can be spread easily so that digital literacy is one of the skills that needs to be trained. The purpose of this research is to produce an interactive e-book on plant growth and development material to train student's digital literacy skills that are valid, practical and effective. This research refers to the 4D development model (Define, Design, Develop and Disseminate). The validity of the interactive e-book was obtained from the validation of two expert biology lecturers. The practicality of the e-book was obtained from a readability test using Fry's formulas and graphs as well as a response questionnaire students. The effectiveness of the interactive e-book was obtained from the calculation of N-gain pretest and posttest results from 16 heterogeneous students in class XII at SMA Negeri 1 Bojonegoro. Data validity, practicality and effectiveness were analyzed descriptively quantitatively. The results of the validity show an average overall score of 97.50% with a very valid category. The practicality of the interactive e-book that was developed received an average response from students of 98.82% in a very positive category and the readability test level from the fry chart showed level 12. The N-gain of pretest-posttest score average is 0.71 in the high category and the interpretation of the average value of each component of digital literacy is in the medium to high category.